If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 = 39y + 16x Reorder the terms: 100 = 16x + 39y Solving 100 = 16x + 39y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 100 + -16x = 16x + -16x + 39y Combine like terms: 16x + -16x = 0 100 + -16x = 0 + 39y 100 + -16x = 39y Add '-100' to each side of the equation. 100 + -100 + -16x = -100 + 39y Combine like terms: 100 + -100 = 0 0 + -16x = -100 + 39y -16x = -100 + 39y Divide each side by '-16'. x = 6.25 + -2.4375y Simplifying x = 6.25 + -2.4375y
| 7-8x-5-7x=5 | | 28-6(w+3)=16+3(2w-12) | | 19y-3(4-3y)=2(9+7y)+19 | | 6s-4(1-3s)=5(s+3) | | 19*6=x | | 15-(a-2)=2(a+1) | | 11=5x-6 | | 3x^2+x=27 | | 3w-6+w=12 | | 4(4x+1)=2x-7x | | 18-6y+7=4y-25 | | 39+12q+65=8+4q | | 3x-14+2x=-14+5x | | 8-5u=8u-31 | | 4(3x+1)=5x-7x | | 22d+42=17d+27 | | 7p+23=p+65 | | 5(4x+1)=5x-7 | | by=x-v | | 10=4 | | 2y+7*15=4 | | 7x(4x+1)=4x-8x | | 2y+70=4 | | 35-2z=5z | | 8(3x+1)=3x-6x | | 2AB^2+3A^2B=5A^3B^3 | | 2x-5(x+3)=-20 | | 5x+2x=4x+30 | | 6(2+7x)=3(5x+4) | | 7(4x+1)=2x-8 | | 19x-4=10x-22 | | x^2+11-12= |